2017
DOI: 10.1099/jmmcr.0.005084
|View full text |Cite
|
Sign up to set email alerts
|

Chromobacterium violaceum infection in chronic granulomatous disease: a case report and review of the literature

Abstract: Introduction. Chromobacterium violaceum is an opportunistic human pathogen, associated with significant mortality, and has been reported in patients with chronic granulomatous disease (CGD), a genetic condition causing impaired phagocytosis.Case presentation. A 28-year-old man with a history of CGD presented with fever, pharyngitis, cervical lymphadenopathy and internal jugular vein thrombosis, following travel to the rural Solomon Islands. C. violaceum was recovered from his blood. The patient recovered after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 20 publications
0
29
0
4
Order By: Relevance
“…Other bacteria found in soil and brackish water that uncommonly cause disease in healthy individuals but are more common pathogens in CGD are Granulibacter bethesdensis, Chromobacterium violaceum, and Francisella philomiragia. [43][44][45] While most of the cases of Chromobacterium violaceum within the US have been primarily described in the southeastern United States, this facultatively anaerobic, Gram-negative bacillus can also be found in tropical and sub-tropical soil worldwide. 44,46 Granulibacter bethesdensis, a fastidious Gram-negative organism that causes indolent lymphadenitis and splenitis in CGD occurs in the US and Europe, but its natural reservoir is unknown.…”
Section: Pathogen Variability Within the United Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other bacteria found in soil and brackish water that uncommonly cause disease in healthy individuals but are more common pathogens in CGD are Granulibacter bethesdensis, Chromobacterium violaceum, and Francisella philomiragia. [43][44][45] While most of the cases of Chromobacterium violaceum within the US have been primarily described in the southeastern United States, this facultatively anaerobic, Gram-negative bacillus can also be found in tropical and sub-tropical soil worldwide. 44,46 Granulibacter bethesdensis, a fastidious Gram-negative organism that causes indolent lymphadenitis and splenitis in CGD occurs in the US and Europe, but its natural reservoir is unknown.…”
Section: Pathogen Variability Within the United Statesmentioning
confidence: 99%
“… 43 45 While most of the cases of Chromobacterium violaceum within the US have been primarily described in the southeastern United States, this facultatively anaerobic, Gram-negative bacillus can also be found in tropical and sub-tropical soil worldwide. 44 , 46 Granulibacter bethesdensis , a fastidious Gram-negative organism that causes indolent lymphadenitis and splenitis in CGD occurs in the US and Europe, but its natural reservoir is unknown. 45 …”
Section: Pathogen Variability Within the United Statesmentioning
confidence: 99%
“…We found that 9 out of 16 patients did see a healthcare provider (56%) with one of them having been previously hospitalized before being transferred to another facility. and 9 of those 10 patients received antibiotics (56%) [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] .…”
Section: Discussionmentioning
confidence: 99%
“…22 Cases of C. violaceum infection in humans have been reported from Australia, India, Nepal, USA, Brazil, and Congo. [23][24][25][26][27][28][29][30][31] There have been about 150 cases reported worldwide. 4 and mortality rate in such cases is found to be high (53%).…”
Section: Clinical Reportsmentioning
confidence: 99%